Joint Instability and Osteoarthritis - Blalock, Darryl (Clin Med Insights Arthritis Musculoskelet Disord, 2015)
Joint instability creates a clinical and economic burden in the health care system. Injuries and disorders that directly damage the joint structure or lead to joint instability are highly associated with osteoarthritis (OA). Thus, understanding the physiology of joint stability and the mechanisms of joint instability-induced OA is of clinical significance. The first section of this review discusses the structure and function of major joint tissues, including periarticular muscles, which play a significant role in joint stability. Because the knee, ankle, and shoulder joints demonstrate a high incidence of ligament injury and joint instability, the second section summarizes the mechanisms of ligament injury-associated joint instability of these joints. The final section highlights the recent advances in the understanding of the mechanical and biological mechanisms of joint instability-induced OA. These advances may lead to new opportunities for clinical intervention in the prevention and early treatment of OA.